A practical guide to botulinum neurotoxin treatment of shoulder spasticity 2: Injection techniques, outcome measurement scales, and case studies - Wissel, Jörg; Camões-Barbosa, Alexandre; Carda, Stefano; Hoad, Damon; Jacinto, Jorge (Frontiers in Neurology, 2022)
Botulinum neurotoxin type A (BoNT-A) is a first-line treatment option for post-stroke spasticity, reducing pain and involuntary movements and helping to restore function. BoNT-A is frequently injected into the arm, wrist, hand and/or finger muscles, but less often into the shoulder muscles, despite clinical trials demonstrating improvements in pain and function after shoulder BoNT-A injection. In part 2 of this two-part practical guide, we present an experts’ consensus on choice of outcome measurement scales and goal setting recommendations for BoNT-A in the treatment of shoulder spasticity to increase awareness of shoulder muscle injection with BoNT-A, alongside the more commonly injected upper limb muscles. Expert consensus was obtained from five European experts with a cumulative experience of more than 100 years of BoNT-A use in post-stroke spasticity. Case studies are included as examples of approaches taken in the treatment of shoulder spasticity. Although velocity-dependent increase in muscle tone is often a focus of patient assessment, it is only one component of spasticity and should be assessed as part of a wider range of measurements. For outcome measurement following BoNT-A injection in shoulder muscles, shoulder-specific scales are recommended. Other scales to be considered include Pain Numerical Rating and/or global functioning, as well as quality of life and global perception of benefit scores. Goal setting is an essential part of the multidisciplinary management process for spasticity; goals should be patient-centric, realistic and achievable; functional-focused goal statements and a mixture of short- (3- to 6-month) and long-term (9- to 18-month) goals are recommended. These can be grouped into symptomatic, passive function, active function, involuntary movement and global mobility. Clinical evaluation tools, goal setting and outcome expectations for the multipattern treatment of shoulder spasticity with BoNT-A should be defined by the whole multidisciplinary team, ensuring patient and caregiver involvement. These recommendations will be of benefit for clinicians who may not be experienced in evaluating and treating spastic shoulders.